Iron-sulfur cluster disassembly in the FNR protein of Escherichia coli by O(2): [4Fe-4S] to [2Fe-2S] conversion with loss of biological activity - Khoroshilova, Natalia (The National Academy of Sciences of the USA, 1997)
The transcription factor FNR (fumarate nitrate reduction) requires the presence of an iron-sulfur (Fe-S) cluster for its function as a global transcription regulator in Escherichia coli when oxygen becomes scarce. To define the oxidation state and type of Fe-S cluster present in the active form of FNR, we have studied anaerobically purified FNR with Mössbauer spectroscopy. Our data showed that this form of FNR contained a [4Fe-4S](2+) cluster (δ = 0.45 mm/s; ΔE(Q) = 1.22 mm/s) and that the [4Fe-4S](2+) cluster was rapidly destroyed on exposure of FNR to air. Under these conditions, the yellow–green active form of FNR turned deep red; analysis of sulfide indicated that 70% of the labile sulfide was still present, suggesting that the Fe-S cluster had been converted into a different form. Little [3Fe-4S] cluster was, however, detected by EPR. According to Mössbauer spectroscopy, the [4Fe-4S](2+) cluster was converted in about 60% yield to a [2Fe-2S](2+) cluster (δ = 0.28 mm/s; ΔE(Q) = 0.58 mm/s) following 17 min of exposure to air. The [2Fe-2S](2+) cluster form of FNR was much more stable to oxygen, but was unable to sustain biological activity (e.g., DNA binding). However, DNA binding and the absorption spectrum characteristic of the [4Fe-4S](2+) cluster could be largely restored from the [2Fe-2S](2+) form when Cys, Fe, DTT, and the NifS protein were added. It has yet to be determined whether the form of FNR containing the [2Fe-2S](2+) cluster has any biological significance, e.g., as an in vivo intermediate that is more rapidly converted to the active form than the apoprotein.